An Analysis of Students’ Ability in Writing Descriptive Texts - Yusri Apriani Margaretha Turnip; Fransiska Vanny Guitara Marbun; Anita Lovia Girsang; Sri Ninta Tarigan (Linguistic, English Education and Art (LEEA) Journal, 2019)
The research was conducted aiming to an analysis of students’ ability in writing descriptive texts at the second grade SMP Swasta Talitakum medan”. The method used in this research is qualitative method. This research was conducted at the second grade focus on generic structure, characteristics, vocabulary. From the data analysis of 23 students, 43.48% of students had a low writing ability category, 34.78% had a medium writing ability, and 21.73% had a high writing ability category. The researchers found that students still had many difficulties in making paragraphs that used the correct generic structure. So students need a lot of practice both at home and courses. Keywords: writing, descriptive text, generic structure.